2016
DOI: 10.1002/jmv.24648
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of LIAISON® XL system for HBsAg, and anti‐HCV and anti‐HIV/Ag p24

Abstract: The aim of this study was to compare the data obtained using the new LIAISON® XL chemiluminescence system to search for HBsAg, anti-HCV, and anti-HIV1-2/p24 Ag with those obtained using the VITROS system currently adopted by the Microbiology Unit of the Hospital of Legnano. Routine samples of patients who were referred by practitioners for the determination of HBsAg (1,000 samples) and/or anti-HCV (1,002 samples) and/or anti-HIV1-2 (995 samples) were simultaneously analyzed using both systems. The concordant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It is not known why the eradication is not complete, but it has been hypothesised that the occurrence of mutants in the S region may explain the persistence of viremia, although it has also been reported that more than half of the subjects without apparent mutations in the S gene have OBIs [36]. We re-tested our HBV DNA-positive and HBsAg-negative samples using a different test from that used in the previous study that is capable of detecting the most frequent mutants of HBV [42] because it has been suggested that HBsAg should be tested in this way [2]. With this test all samples were negative according to OBIs are characterised by undetectable HBV DNA and non-mutated HBsAg levels [11].…”
Section: Discussionmentioning
confidence: 98%
“…It is not known why the eradication is not complete, but it has been hypothesised that the occurrence of mutants in the S region may explain the persistence of viremia, although it has also been reported that more than half of the subjects without apparent mutations in the S gene have OBIs [36]. We re-tested our HBV DNA-positive and HBsAg-negative samples using a different test from that used in the previous study that is capable of detecting the most frequent mutants of HBV [42] because it has been suggested that HBsAg should be tested in this way [2]. With this test all samples were negative according to OBIs are characterised by undetectable HBV DNA and non-mutated HBsAg levels [11].…”
Section: Discussionmentioning
confidence: 98%
“…As new immunoassay or chemiluminescence screening tests from companies such as Ortho, Abbott and Bayer come onto the market, the tables of threshold values (such as the S/CO ratio) have been updated using the values for each, but there are no indications concerning the recently available chemiluminescence test of DiaSorin. The performance of this system in detecting infectious disease has been previously tested, but not for this specific purpose. The aim of this study was to determine a threshold value for the DiaSorin LIAISON XL anti‐HCV test above which at least 95% of the samples are positive to an additional antibody test.…”
Section: Introductionmentioning
confidence: 99%